Effect of three storage methods on fruit decay and brown rot of apple - Balla, B.; Holb, I. J. (International Journal of Horticultural Science, 2007)
The aim of our two-year study was to evaluate fruit decay and Monilinia fruit rot in three controlled atmospheres (CA), ultra-low oxygen (ULO) and traditional storage methods on apples for a duration of several months storage period. Four phytopathological treatments were studied under each storage condition: 1) 48 healthy fruit per unit, 2) 48 injured fruit per unit, 3) 47 healthy fruit and 1 brown rotted fruit per unit, and 4) 47 injured fruit and 1 brown rotted fruit per unit. Our results clearly demonstrated that fruit loss during storage is highly influenced by storage conditions and health status of the stored fruits. In the 2005 experiment, the lowest and largest fruit decay occurred under the ULO and traditional storage conditions, respectively (Table 1). The fruit decay was significantly different for the different storage methods. Fruit decay was fully suppressed in ULO storage except in the treatments of injured and injured + 1 brown rotted apple. Under CA and traditional storage conditions, when healthy fruit was stored, fruit decay was significantly lower compared with injured fruit including 1 brown rotted fruits. However, half of the fruit decay was caused by M. fructigena in CA store irrespective to phytopathogenic treatments. In 2006, results were not so consistent on cv. Idared but were not essentially different from the 2005 experiments.